2007
DOI: 10.5040/9781492596844
|View full text |Cite
|
Sign up to set email alerts
|

Attention and Motor Skill Learning

Abstract: Attention and Motor Skill Learning explores how a person's focus of attention affects motor performance and, in particular, the learning of motor skills. It synthesizes the knowledge coming from recent research examining the effects of attentional focus on motor performance and learning, and it provides practical implications for both instructional and rehabilitative settings. Attention and Motor Skill Learning challenges traditional views that the method of learning a motor skill involves focusing a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

17
212
1
25

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 295 publications
(266 citation statements)
references
References 0 publications
17
212
1
25
Order By: Relevance
“…These considerations highlight the importance of using manipulations that are defined in relation to both the internal/external dimension and the association/dissociation dimension (Stevinson & Biddle, 1998). Wulf (2007a) offers one potential source for researchers in which she has provided an example of instructional manipulations for various sports and exercises that will induce an internal association and external association focus of attention. Schücker et al (2009) did not find any significant difference in oxygen consumption between a focus on running movement and a focus on breathing.…”
Section: Discussionmentioning
confidence: 99%
“…These considerations highlight the importance of using manipulations that are defined in relation to both the internal/external dimension and the association/dissociation dimension (Stevinson & Biddle, 1998). Wulf (2007a) offers one potential source for researchers in which she has provided an example of instructional manipulations for various sports and exercises that will induce an internal association and external association focus of attention. Schücker et al (2009) did not find any significant difference in oxygen consumption between a focus on running movement and a focus on breathing.…”
Section: Discussionmentioning
confidence: 99%
“…an implement)inducing an 'external focus' -generally results in more effective performance and learning. 27 Many studies examining attentional focus effects have used complex motor skills. They have shown that a simple change in the wording of instructions can have a significant impact on performance and learning.…”
Section: Focus Of Attentionmentioning
confidence: 99%
“…32 The advantages of an external focus have been shown for different levels of expertise and populations (including children and persons with motor impairments), 33 as well as for performance under pressure. 27 An external focus of attention appears to speed up the learning process -or shorten the first stages of learning -by facilitating movement automaticity ('constrained action hypothesis'). 34 More specifically, a focus on the movement effect promotes the utilisation of unconscious or automatic processes, whereas an internal focus on one's own movements results in a more conscious type of control that .…”
Section: Focus Of Attentionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies (such as Beilock et al 2004, 2007, Ford et al 2005, Baumeister 1984, Masters 1992, Wulf & Prinz 2001, Beilock & DeCaro, 2007 might be seen as supporting an affirmative answer to this question. As the psychologists Sian Beilock (2010) explains it, "highly practiced skills become automatic, so performance may actually be damaged by introspection, which is characteristic of an earlier, consciously-mediated stage."…”
mentioning
confidence: 99%